KASUS “SI PENENDANG SESAJEN” SEBAGAI REFLEKSI PEMBELAJARAN GUNA MENJAGA MUTU EKSISTENSI MODERASI BERAGAMA DI INDONESIA - I Dewa Gede Darma Permana dewa_permana21 (UHN IGB Sugriwa Denpasar, 2022)
Abstract Indonesia is a unique country, where differences and diversity can coexist within the framework of unity. However, diversity in Indonesia, especially in terms of belief, can also trigger disharmony conflicts in the form of cases of blasphemy. The case of Hadfana Fairus